Molecular differentiation of Turkey cattle isolates of Fasciola hepatica and Fasciola gigantica - Simsek, S.; Utuk, A. E.; Balkaya, I. (Versita, 2011)
The most common and widespread liver flukes of the genus Fasciola are Fasciola hepatica and F. gigantica. Adults of both species occur in many domestic ruminants and in humans and can cause serious disease. The differential diagnosis of these flukes infection is very important because of their different transmission and epidemiological characteristics. A simple and rapid PCR-restriction fragment length polymorphism (RFLP) assay, using the common restriction enzymes AluI and RsaI, is described to distinguish between both fasciolid species. After the digestion of the mitochondrial cytochrome c oxidase 1 (CO1) PCR product with the restriction enzyme AluI, the RFLP profile obtained from F. hepatica revealed two fragments, whereas F. gigantica was not cut. The RsaI digestion generated two fragments from F. gigantica, whereas it did not cut the PCR product from F. hepatica. Results were confirmed with CO1 sequence analysis of both F. hepatica and F. gigantica. The present study suggests that the PCR-RFLP method described here can be used for the proper identification of Fasciola species.
Keywords: Fasciola hepatica; Fasciola gigantica; PCR-RFLP; cattle; Turkey